The effect of teacher designed multimedia on student comprehension and retention rates within introductory college science courses - Rhodes, Ashley E. (Kansas State University, 2013)
Compared to other nations, fewer American students are pursuing and completing degrees within the science, technology, engineering, and mathematics (STEM) fields. For the United States to remain competitive, the development of novel instructional techniques designed to reach students who might otherwise be lost from these majors is imperative. This study examined the use of teacher designed multimedia within an introductory STEM course. Quantitative methods were used in a real classroom setting to examine the relationship between the use of multimedia and the amount of information students comprehended and retained when learning photosynthesis. Also, the relationship between the use of multimedia and the learning gains of female students within introductory STEM courses was examined, as their participation within the STEM fields has historically been low. Qualitative methods were employed to discern which multimedia features students and instructors found the most beneficial regarding the presentation of complex and abstract scientific concepts. Using a quasi-experimental, design-based research approach, it was determined that the use of simple animations and corresponding narration increased student learning gains compared to the use of static pictures and text. This finding aligned well with theories regarding multimedia learning and its use of dual coding for reducing cognitive load. The value of multimedia for learning gains was greatest for females with lower prior knowledge levels, as defined by performance on a pre-test. However male students with low prior knowledge benefited, although not to the same degree as females. In agreement with the fundamentals of constructivism, this finding supported the idea that basic schema construction is paramount for increasing comprehension. Results from the qualitative portion of the study indicated that students prefer multimedia over static text and pictures because: 1. Complex processes can unfold in motion while being described verbally 2. Schema construction is guided by a trusted source, and 3. Small chunks of information can be presented yet tied together in a larger sequence.
Keywords: Multimedia; Science; Instruction; Education, Technology (0710)